Roger Casement: How His Family Saw His Role in 1916 - Casement, Susie (ABEI Journal, 2016)
This is a personal statement on the family tree of Roger Casement, a member of my family. Silence in the past, pride in the present.Keywords: Roger Casement; family tree.